CD9 shapes glucocorticoid sensitivity in pediatric B-cell precursor acute lymphoblastic leukemia - Zhang, Chi; Chan, Kathy Yuen Yee; Ng, Wing Hei; Cheung, John Tak Kit; Sun, Qiwei; Wang, Han; Chung, Po Yee; Cheng, Frankie Wai Tsoi; Leung, Alex Wing Kwan; Zhang, Xiao-Bing; Lee, Po Yi; Fok, Siu Ping; et al. (Haematologica, 2024)
Resistance to glucocorticoids (GC), the common agents for remission induction in pediatric B-cell precursor acute lymphoblastic leukemia (BCP-ALL), poses a significant therapeutic hurdle. Therefore, dissecting the mechanisms shaping GC resistance could lead to new treatment modalities. Here, we showed that CD9- BCP-ALL cells were preferentially resistant to prednisone and dexamethasone over other standard cytotoxic agents. Concordantly, we identified significantly more poor responders to the prednisone prephase among BCP-ALL patients with a CD9- phenotype, especially for those with adverse presenting features including older age, higher white cell count and BCR-ABL1. Furthermore, gain- and loss-offunction experiments dictated a definitive functional linkage between CD9 expression and GC susceptibility, as demonstrated by the reversal and acquisition of relative GC resistance in CD9low and CD9high BCP-ALL cells, respectively. Despite physical binding to the GC receptor NR3C1, CD9 did not alter its expression, phosphorylation or nuclear translocation but potentiated the induction of GC-responsive genes in GC-resistant cells. Importantly, the MEK inhibitor trametinib exhibited higher synergy with GC against CD9- than CD9+ lymphoblasts to reverse drug resistance in vitro and in vivo. Collectively, our results elucidate a previously unrecognized regulatory function of CD9 in GC sensitivity, and inform new strategies for management of children with resistant BCP-ALL.
Keywords: Drug Resistance, Neoplasm; Animals; Receptors, Glucocorticoid; Female; dítě; antigeny CD9; předškolní dítě; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Cell Line, Tumor; receptory glukokortikoidů; Tetraspanin 29; ženské pohlaví; lidé; Mice; glukokortikoidy; chemorezistence; Glucocorticoids; myši; Male; dexamethason; Child, Preschool; Dexamethasone; Child; zvířata; pre-B-buněčná leukemie; mužské pohlaví; nádorové buněčné linie; Humans